2019
DOI: 10.1016/j.cgh.2018.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Combination Treatment With Calcineurin Inhibitors and Vedolizumab in Patients With Refractory Inflammatory Bowel Disease

Abstract: Combination therapy of vedolizumab with either cyclosporin or tacrolimus is effective and safe at inducing and maintaining clinical remission in patients with CD and UC with up to 52 weeks of follow-up evaluation. Larger studies of the ability of calcineurin inhibitors to induce remission in patients on vedolizumab are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 28 publications
1
47
0
1
Order By: Relevance
“…However, both studies had limitations, including small patient numbers and limited follow‐up time. The earlier study from our group by Christensen et al reported on nine patients with Crohn's disease and 11 patients with ulcerative colitis treated with combination therapy of vedolizumab with either ciclosporin or tacrolimus, and found that by week 14 of treatment, four (44%) patients with Crohn's disease and six (55%) patients with ulcerative colitis were in clinical remission.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…However, both studies had limitations, including small patient numbers and limited follow‐up time. The earlier study from our group by Christensen et al reported on nine patients with Crohn's disease and 11 patients with ulcerative colitis treated with combination therapy of vedolizumab with either ciclosporin or tacrolimus, and found that by week 14 of treatment, four (44%) patients with Crohn's disease and six (55%) patients with ulcerative colitis were in clinical remission.…”
Section: Discussionmentioning
confidence: 92%
“…There have been two previous studies and a case series of two patients that demonstrated the feasibility of inducing remission with ciclosporin followed by maintenance of remission with vedolizumab. However, both studies had limitations, including small patient numbers and limited follow‐up time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations